Normalising desistance: contextualising marijuana and cocaine use careers in young adults. Issue 6 (1st April 2016) - Roussell, Aaron; Omori, Marisa
Abstract: Although there is a vast literature on drug use and addiction, there is little work that addresses the long‐term use of drugs within the general population. We take a more contextual look in examining longitudinal drug use patterns over the course of 14 years for a representative sample of young adults in their late teens and early twenties in the United States using the National Longitudinal Survey of Youth (NLSY). We use a growth trajectory modelling approach for cocaine and marijuana users to determine general use careers. Using contextual and life‐course variables, we then estimate a multinomial logistic regression model to predict group membership. In addition to establishing general use career groups, we ask how well mainstream theories comport with our findings and how the different chemical makeup of cocaine and marijuana influence our findings. We find four general use career groups: (i) high use/late desistance; (ii) peaked use/strong desistance; (iii) low use; and (iv) stable use/gradual desistance. Our results suggest similar careers for users of both drugs, with desistance over time as the rule for all groups. We also find some support for life‐course and contextual factors in drug using patterns, but our findings challenge other psychological and criminological theories.